UN Peacekeeping Operations as a Tool for Securing Peace (Czech Journal of International Relations, 2024)
The UN, Peace and Force. Editor Michael Pugit. Frank Cass mul Co., Ltd, London 1997,209 stran, ISBN O 7146 4759 4.